Business-to-business marketing - Brennan, Ross; Canning, Louise; McGrath, Helen (SAGE Publications, 2024)
Written from a European perspective, this comprehensive and regularly updated textbook covers both the theory and practice of global business-to-business (b2b) marketing. New to this sixth edition: Increased and updated coverage covering digital transformation and responsible business as well as new content on small firms. New examples and case studies covering small firms in business markets. New organizational coverage, including companies and brands such as Airspares Unlimited, Optel Group, Pfizer, Royal FloraHolland, Toyota, Trellebord, ValCo Engineering Ltd and Volkswagen. Updated online resources for instructors to use and share in their teaching with students, including PowerPoint slides, a testbank, and an instructor's manual containing guidance and links to online content such as video marterial, reports, websites and relevant journal articles for each chapter. The textbook is suitable for students taking a b2b/industrial marketing module at undergraduate or postgraduate levels. It will also be useful to researchers and practitioners involved in b2b/industrial marketing"--